2022
DOI: 10.1002/jcla.24691
|View full text |Cite
|
Sign up to set email alerts
|

High expression of DARS2 indicates poor prognosis in lung adenocarcinoma

Abstract: Background DARS2 was overexpressed in multiple tumor types, but the biological role of DARS2 in lung adenocarcinoma (LUAD) have not been elucidated. Methods Firstly, the DARS2 expression in LUAD was explored using The Cancer Genome Atlas (TCGA). Then, qRT‐PCR and Western blot were performed to confirm DARS2 expression in LUAD. Next, Cox regression and Kaplan–Meier methods were utilized to evaluate whether DARS2 expression can affect the overall survival. The relationships between DARS2 expression and clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…DARS2 has been identified as a hepatocellular carcinoma (HCC) oncogene that promotes HCC cell cycle progression and inhibits HCC cell apoptosis (83). In lung adenocarcinoma cells, DARS2 is involved in proliferation, invasion, and apoptosis and shows promise as a therapeutic target (84). MAFF could promote tumor invasion and metastasis through IL11 and STAT3 signaling (85).…”
Section: Discussionmentioning
confidence: 99%
“…DARS2 has been identified as a hepatocellular carcinoma (HCC) oncogene that promotes HCC cell cycle progression and inhibits HCC cell apoptosis (83). In lung adenocarcinoma cells, DARS2 is involved in proliferation, invasion, and apoptosis and shows promise as a therapeutic target (84). MAFF could promote tumor invasion and metastasis through IL11 and STAT3 signaling (85).…”
Section: Discussionmentioning
confidence: 99%
“…DARS2 is responsible for producing the enzyme that ensures the correct translation of the genetic code by attaching amino acids to their corresponding tRNA molecules in the mitochondria ( 9 , 11 , 24 ). Liu and colleagues discovered that DARS2 can serve as a prognostic marker for non-adenocarcinomas and promote the proliferation, invasion, and migration of lung adenocarcinoma cells while inhibiting cell apoptosis ( 17 , 25 , 26 ). It suggests that DARS2 may be proposed as a new biomarker to distinguish between multiple myeloma and lung adenocarcinoma ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that DARS2 may be proposed as a new biomarker to distinguish between multiple myeloma and lung adenocarcinoma ( 27 ). It has been found that DARS2 is an oncogene in hepatocellular carcinoma and can promote the progression of the hepatocellular carcinoma cell cycle while inhibiting apoptosis in HCC cells ( 16 , 17 ). Although Wu’s team discovered that DARS2 can predict overall survival in BLCA and serve as a predictive model for assessing clinical outcomes ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al analyzed the TCGA dataset and found that DARS2 was highly expressed in LUAD samples, and its expression level was related to tumor stage, T stage, and M stage. However, the relationship between DARS2 and clinicopathological characteristics was not verified by clinical cohort [ 35 ].…”
Section: Discussionmentioning
confidence: 99%